Assessing Variability in Vascular Response to Cocoa With Personal Devices: A Series of Double-Blind Randomized Crossover n-of-1 Trials - Bapir, Mariam; Campagnolo, Paola; Rodriguez-Mateos, Ana; Skene, Simon S.; Heiss, Christian (Frontiers in Nutrition, 2022)
Controlled clinical intervention studies have demonstrated that cocoa flavanols (CF) can decrease blood pressure and arterial stiffness in healthy humans, although a large variability in the effect size across trials has been reported. In this study, we evaluated the intra- and inter-individual variability of responses to CF in everyday life using a series of n-of-1 trials in healthy free-living individuals with normal blood pressure carrying personal devices. In total, eleven healthy young humans participated in a repeated crossover randomized controlled double-blind n-of-1 trial. On 8 consecutive days, each volunteer consumed on alternating days 6 CF capsules (862 mg CF) on 4 days and 6 matched placebo capsules (P, 0 mg CF/day) on another 4 days in one of the two randomized sequences (CF-P-CF-P-CF-P-CF-P or P-CF-P-CF-P-CF-P-CF). On each day, the capsules were taken at the same time in the morning with breakfast after baseline measurements. Each subject was provided with an upper arm blood pressure monitor and a finger clip that measures pulse wave velocity (PWV). Measurements of blood pressure, heart rate, and PWV were taken at least hourly over 12 h during the day by the participants. On the first 2 days, measurements were performed under supervision to provide training. The overall mixed model analysis showed that CF significantly decreased 12-h systolic blood pressure and PWV by −1.4 ± 0.3 mmHg and −0.11 ± 0.03 m/s, respectively. Peak effects were observed within the first 3 h (1.5 h SBP: −4.9 ± 2.2 mmHg, PWV: −0.32 ± 0.17 m/s) and again after 8 h post-ingestion. Large inter-individual variation in responses was found [intra-cluster correlation coefficients (ICC): 0.41, 0.41]. When analyzing single individuals’ datasets, there was also considerable between-day variation in individual responses that varied greatly between subjects (ICC: 0–0.30, 0–0.22, 0–0.45). Effect sizes inversely correlated with baseline blood pressure values both between- and within-subjects. The data confirm that cocoa can decrease blood pressure and arterial stiffness in everyday life when elevated within the normal range. The large inter- and intra-individual variation in responses calls for more personalized nutritional intervention strategies.